Association between APOE e4 Gene Dose, Beta-Amyloid, and Cognitive Performance in Healthy Elderly Volunteers - Lehtonen, Riina (My University, 2024)
If disease-modifying drugs for Alzheimer’s Disease (AD) will be approved in the future, the pathological disease process could be prevented more efficiently if treatments would be initiated in the earliest phases of the disease, which requires identifying the early asymptomatic phase. The ε4 allele of Apolipoprotein E (APOE) is the strongest genetic risk factor for late-onset AD. This study aimed to investigate the influence of the number of the APOE ε4 alleles on domain-specific cognition, and whether the level of brain beta-amyloid (Aβ) depositions is associated with domain-specific cognition in the sample of 59 cognitively healthy elderly with varying APOE genotypes. A broad battery of neuropsychological tests was used to measure cognitive performance, and positron emission tomography was used to estimate brain Aβ levels. Cognitive domains in this study included episodic memory, executive functions, language, and processing speed. No significant differences in these cognitive domains were found between different APOE genotypes. Only episodic memory correlated significantly with brain Aβ accumulation. However, after adjusting with other factors, the association between Aβ and episodic memory was no more significant, and the association was most moderated by education level. These findings together with previous research suggest that the APOE ε4 allele-related subtle cognitive decline may not be evident in the earliest phases of AD even in the presence of brain Aβ pathology, and that cognitive performance in clinically normal elderly is moderated by several factors.
Keywords: Alzheimer’s Disease, Memory Disorder, Beta-Amyloid, APOE, Apolipoprotein E, Positron Emission Tomography, Neuropathology, Cognitive Domain, Subtle Cognitive Decline, Episodic Memory, Executive Functions, Language, Processing Speed, Preclinical Alzheimer’s Disease